POLA PEMANFAATAN RUANG TERBUKA HIJAU PADA KAWASAN PERKAMPUNGAN PLEMBURAN TEGAL,NGAGLIK SLEMAN - Budi Santoso, Retna Hidayah, Sumardjito (Universitas Negeri Yogyakarta, 2012)
This paper aims to describe the utilization of open space in Plemburan Tegal,Ngaglik Sleman. This description that will be the basis to determine the utilizationpattern of green open space in accordance with land use regulation is done by thefollowing steps: identified land use, identified existing physical condition of the openspace, identified residents activities in open space areas, and finally perform trendanalysis to determine the pattern use of green space utilization. The study wasconducted in inductive approach as well as qualitative descriptive method. Theresults show that Plemburan Tegal has adequate open space of 33.13% of totalarea, consist of green area 20.57% and paved area 12.56%. Based to the openownership, the open space classified into 45.74% belongs to the privat while54.26% belongs to the public. Based on the land use pattern and activities, openspace of Plemburan Tegal is classified into following used: adult gathering activities(RTH1), community hall completed by outdoor sport activities of tennis and volleyball (RTH 2), playground activities for children (RTH 7), individual-based plantations,and vacant open space.Keyword: Green open space, Land use